2003
DOI: 10.1191/0961203303lu498oa
|View full text |Cite
|
Sign up to set email alerts
|

MRI and the brain in systemic lupus erythematosus

Abstract: Systemic lupus erythematosus (SLE) can affect any part of the central nervous system (CNS) from the cerebrum to the cauda eqina, giving rise to diverse neurological mainfestations. Despite clinically apparent symptoms and signs, imaging will commonly be normal while at times the magnitude of changes demonstrated on MRI may be out of proportion to the clinical presentation. We describe the MRI techniques used in CNS imaging and the pattern of presentation in SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
9

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 5 publications
2
28
0
9
Order By: Relevance
“…3 Although various neurological manifestations occur in 50-70% of cases of SLE, the brain MRI remains normal. 4 The patient's history of SLE raised this possibility, although clinically the disease appeared quiescent. A low cognitive score for an individual is a poor predictor of the presence of CNS involvement.…”
Section: Discussionmentioning
confidence: 99%
“…3 Although various neurological manifestations occur in 50-70% of cases of SLE, the brain MRI remains normal. 4 The patient's history of SLE raised this possibility, although clinically the disease appeared quiescent. A low cognitive score for an individual is a poor predictor of the presence of CNS involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristic histological changes include proliferations of intimal cells, increased fibrous tissue and mucoid hyperplasia; the lumen may become occluded by fibrin thrombi, and the vessel may be surrounded by microglia clusters, inflammatory infiltrates, small infarcts or necrosis [26, 27]. MRI studies have shown a high prevalence of hyperintense lesions in T 2 -weighted and FLAIR sequences related to small infarcts in pathological studies [28], findings which are thought to result from this cerebral vasculopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Несомнено, моделот на клинички манифестации се рефлектира во можностите на МР: локализирани невролошки знаци и напади се поврзани со фокални абнормалности на МР почесто од колку дифузни промени. Сепак, не постои стандардизиран МР модел, кој е дијагностички специфичнен за невролупус [36,37]. Сепак, некои карактеристични промени се земаат во разгледување како: кај акутните лезии немање на дискретни граници, има среден интензитет на Т2 снимки, имаат елипсоидна форма и се наоѓаат на границата меѓу кортексот и белата маса, или во белата маса.…”
Section: снимања на мозочниот паренхимunclassified